Kunst og cellekultur - Pernille Leth-Espensen (Periskop, 2019)
This article discusses a range of artworks made by the artist group The Tissue Culture & Art Project, artworks that literally grow, as they are created with living cells. It is argued that the artworks address growth from different perspectives. They address the preconditions for growth of cells in vitro; they address how negative or monstrous growth in one context may be positive in another and vice versa; and, finally, the artworks problematise lab-grown meat as a solution to ethical issues and climate problems caused by economic growth.